Feasibility of robotic‐assisted atrial septal defect repair in a 6‐year‐old patient. Issue 2 (31st October 2020) - Güllü, Ahmet Ümit; Şenay, Şahin; Ersin, Egemen; Demirhisar, Önder; Kocyigit, Muharrem; Alhan, Cem
Abstract: Background: The feasibility, safety and advantages of minimally invasive or robotic repair of atrial septal defect (ASD) in adults were reported previously. However, there is limited data for the application of these systems in paediatric patients. Although current robotic systems still have large instruments for surgical repair in children, some appropriate patients may benefit from this technology. Method: A 6‐year‐old child with ASD underwent robotic assistant repair via Da‐Vinci Robotic Systems. Venous cannulation was achieved by internal jugular and femoral veins (10F–14F) and arterial cannulation was performed via femoral artery under transesophageal echocardiography (TEE) guidance (10F). A 3 cm incision was made in the right fourth intercostal space, used for working and the camera port in the same time. The ports were placed considering not to damage the potential developing breast tissue. After the port implantation (8F) and cardiac arrest, the ASD repair was completed with primary closure technique. Result: The perioperative period was uneventful and the patient was discharged from hospital 5 days after surgery. Conclusion: ASD closure with robotic assistant was achieved in a large enough sized paediatric patient. With the development of thinner and shorter robotic arms, it will be possible to use robotic assistance more common during the repair of congenital heart diseases.